Somaclonal variations of Soybeans (Glycine Max. L. Merr) stimulated by drought stress based on random amplified polymorphic DNAs (RAPDs) - Arumingtyas, Estri L.; Widoretno, Wahyu; Indriyani, Serafinah (Scientific Research Publishing, 2012)
In soybeans, drought stress causes 50% yield losses. Breeding for drought tolerance in soybeans has been widely developed using various methods, among which is polyethylene glycol (PEG-6000) induction to simulate drought in vitro. In a previous experiment, three somaclones with different levels of tolerance were generated. The objectives of this research were to determine the RAPD patterns of those somaclones and to investigate the correlation of the RAPD patterns to the drought tolerance characteristics. The results showed eleven RAPD primers capable of amplifying the DNA genome of soybeans, among which four primers were monomorphic and seven were polymorphic. Two of the polymorphic primers, OPK7 and OPK12, are capable of differentiating medium tolerance traits from other traits. Bands that are specific for medium tolerance against drought were 450 bp and 650 bp in size, generated by the OPK7 primer, and the band of 2000 bp, generated by the OPK12 primer. However, there was no band capable of differentiating between sensitive and tolerance varieties/lines, although some changing of the DNA sequence was detected in this research. This indicates that there are other factors responsible for the expression of drought tolerance.
Keywords: RAPD; Drought Tolerance; Soybeans; Somaclones